2020
DOI: 10.1039/d0cc03994b
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the effects of quadrupolar sinksvia15N relaxation dynamics in metronidazoles hyperpolarizedviaSABRE-SHEATH

Abstract: The presence of 14N nucleus in the scalar coupling network results in a 3-fold decrease of 15N T1 and polarization values for all 15N sites in 15N2-metronidazole versus15N3-metronidazole in SABRE hyperpolarization in microtesla fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
134
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 40 publications
(140 citation statements)
references
References 34 publications
6
134
0
Order By: Relevance
“…To maximize the polarization levels, >2 h of activation of SABRE complex [38, 55] in the presence of [ 15 N 3 ]nimorazole is required (Figure 3 a). This activation time is comparable to that observed with [ 15 N 3 ]metronidazole under similar conditions [56] . The magnetic field profile of polarization transfer in microtesla field range exhibits a clear maximum at ≈0.4 μT for all three 15 N sites (Figure 3 b).…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…To maximize the polarization levels, >2 h of activation of SABRE complex [38, 55] in the presence of [ 15 N 3 ]nimorazole is required (Figure 3 a). This activation time is comparable to that observed with [ 15 N 3 ]metronidazole under similar conditions [56] . The magnetic field profile of polarization transfer in microtesla field range exhibits a clear maximum at ≈0.4 μT for all three 15 N sites (Figure 3 b).…”
Section: Resultssupporting
confidence: 83%
“…First, it is consistent with the fact that these three 15 N nuclei are strongly coupled at microtesla magnetic fields and thus continuously share magnetization with each other via 15 N‐ 15 N spin relays [47, 48] . Second and more importantly, our recent study of [ 15 N 3 ] and [ 15 N 2 ]metronidazole isotopologues clearly demonstrated the detrimental role of 14 N quadrupolar nucleus presence in the spin‐relayed network [56] . In this case, two‐bond 15 N‐ 14 N spin‐spin coupling results in a significantly lower effective 15 N T 1 for all (remaining) 15 N sites in [ 15 N 2 ]metronidazole versus [ 15 N 3 ]metronidazole: 15 N T 1 clustering of 8–9 seconds versus 23–31 seconds, respectively under similar (1:20) catalyst‐to‐substrate ratio as the one studied here [56] .…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…This activation time is comparable to that observed with [ 15 N 3 ]metronidazole under similar conditions. [56] Them agnetic field profile of polarization transfer in microtesla field range exhibits aclear maximum at % 0.4 mT for all three 15 Ns ites (Figure 3b). Them aximum position is the same as that for [ 15 N 3 ]metronidazole, [48] further supporting the similarity in J coupling network between the polarizing 15 Ns pins in these two molecules.M oreover,t he microtesla magnetic field profile is similar for all three 15 Nn uclei of [ 15 N 3 ]nimorazole,s erving as an additional proof of spinrelayed polarization transfer mechanism discussed above.…”
Section: Resultsmentioning
confidence: 92%